Developing reviewing gamification on specific learning differences (SpLDs) for pre-service teachers at slow learners care - Faridha, Haidir Algi Ghaffar; Jamilah, Radhiyatul; Alfariz, Muhammad Fahresy (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
This research develops a language learning gamification model based on the needs analysis of teacher candidate's workshops on Specific Learning Differences (SpLDs). This research used research and development (R&D) method using Kemp's Instructional Design Model, the data analyzed qualitatively from primary data sources include document analyses of reputable books and relevant journal articles. This research revealed that Quizizz's incorporation into pedagogical workshops replaces traditional paper-based quizzes with interactive games, indicating heightened engagement among adults when gamified learning. Each item is accompanied by clear instructions and employs diverse modes like images, videos, or audio to enhance comprehension. This multimodal approach motivates students by facilitating the integration of textual and visual elements in their learning process. Incorporating reviewing designed games, such as Quizizz, in preservice teachers' workshops for SpLDs is a highly inclusive accommodation. The use of diverse multimodalities and carefully designed questions is essential for ensuring inclusivity and accessibility. This approach shows promise for improving student engagement and addressing the needs of learners with SpLDs.